Journal Bearings Lubrication Aspect Analysis Using Non-Newtonian Fluids. (4th February 2013) - Nessil, Abdessamed; Larbi, Salah; Belhaneche, Hacene; Malki, Maamar
Abstract : The aim of this work is related to an analysis of journal bearings lubrication using non-Newtonian fluids which are described by a power-law model. The performance characteristics of the journal bearings are determined for various values of the non-Newtonian power-law index "n " which is equal to: 0.9, 1, and 1.1. Obtained numerical results show that for the dilatant fluids (n > 1 ), the load-carrying capacity, the pressure, the temperature, and the frictional force increased while for the pseudo-plastic fluids (n < 1 ) they decreased. The influence of the thermal effects on these characteristics is important at higher values of the flow behavior index "n ." Obtained results are compared to those obtained by others. Good agreement is observed between the different results.